2021
DOI: 10.1101/2021.11.18.469197
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nonquantal Transmission at the Vestibular Hair Cell-Calyx Synapse: KLV Currents Modulate Fast Electrical and Slow K+ Potentials in the Synaptic Cleft

Abstract: Vestibular hair cells transmit information about head position and motion across synapses to primary afferent neurons. At some of these synapses, the afferent neuron envelopes the hair cell, forming an enlarged synaptic terminal referred to as a calyx. The vestibular hair cell-calyx synapse supports nonquantal transmission (NQT), a neurotransmitter-independent mechanism that is exceptionally fast. The underlying biophysical mechanisms that give rise to NQT are not fully understood. Here we present a computatio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 94 publications
(249 reference statements)
0
4
0
Order By: Relevance
“…Type II hair cells have a more depolarized membrane potential and a smaller activation range ( 47 , 66 , 67 ). We still have much to learn about how calyceal synapses evolved, but one of the driving forces behind their evolution exclusively within the vestibular system may be the need for faster reflexes in a terrestrial environment ( 29 , 47 , 75 ). Further investigations of the relationships between synaptic features, and the geometric and mechanical properties of the hair bundles are required, to shed light on both phylogenic aspects of evolution and morphometric sets for functional outcomes.…”
Section: Evolutionary Changes In the Inner Ear: Structure-function Co...mentioning
confidence: 99%
“…Type II hair cells have a more depolarized membrane potential and a smaller activation range ( 47 , 66 , 67 ). We still have much to learn about how calyceal synapses evolved, but one of the driving forces behind their evolution exclusively within the vestibular system may be the need for faster reflexes in a terrestrial environment ( 29 , 47 , 75 ). Further investigations of the relationships between synaptic features, and the geometric and mechanical properties of the hair bundles are required, to shed light on both phylogenic aspects of evolution and morphometric sets for functional outcomes.…”
Section: Evolutionary Changes In the Inner Ear: Structure-function Co...mentioning
confidence: 99%
“…Rapid inward transduction current would immediately flow out as potassium through HC channels, with much of the current flowing into the extensive synaptic cleft and a minority flowing into the calyx ( Figure 2B ). Such coupling can be analyzed using either Kirchhoff's current or voltage laws, and the conclusion is the same: there would be relatively small voltage gains or drops of a few mV along the cleft depending on the current direction and the precise resistance ( 97 , 110 ). The impact of this on specific channels facing the cleft is unknown and would greatly depend on their position with respect to the apical gap between HC and calyx.…”
Section: Hc and Afferent Depolarization Creates Resistive Coupling Th...mentioning
confidence: 99%
“…2B). Such coupling can be analyzed using either Kirchhoff’s current or voltage laws, and the conclusion is the same: there would be relatively small voltage gains or drops of a few mV along the cleft depending on the current direction and the precise resistance (98, 102). The impact of this on specific channels facing the cleft is unknown and would greatly depend on their position with respect to the apical gap between HC and calyx.…”
Section: Dual-electrode Studiesmentioning
confidence: 99%
“…The theoretical analysis (97,98) relied on equivalent circuits of the Type I HC, cleft, and calyx to analyze the problem primarily as ephaptic transmission (99-101) embellished by potassium accumulation. In general, this analysis concluded that the potential drops associated with current flow along the cleft from HC base to apex created only minor differences in the driving force for channels facing the cleft, and as a result were not likely to be a major source of coupling (98), but see (102). The possibility that ion accumulation could have the effect suggested by Chen was also examined experimentally (103).…”
Section: Theoretical and Single-electrode Studiesmentioning
confidence: 99%